2011
DOI: 10.1002/ange.201101655
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐gesteuerte bivalente Präsentation von Liganden für den Östrogenrezeptor

Abstract: DNA‐Schablone für niedermolekulare Verbindungen: Durch Klick‐Reaktionen wurden Steroidanaloga mit DNA verknüpft und über ternäre DNA‐Komplexe bivalent präsentiert. Die räumliche Rasterung des Östrogenrezeptors zeigte den Abstand zwischen den gebundenen Liganden auf und gab Hinweise auf eine zweite hydrophobe Bindungsstelle. Das Bild zeigt einen DNA(schwarz)‐Raloxifen(orange)‐Komplex in der Ligandenbindungsdomäne des Rezeptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…The use of hybridization to pair ligand and gain in affinity through cooperative interactions with a target is well established. [29][30][31][32][33][34] However, the majority of studies reported so far used relatively long duplexes to achieve stable pairing between ligands. We showed that in one case, this could be reduced to an extremely short length PNA oligomer (4-mer) while preserving the cooperativity.…”
Section: Resultsmentioning
confidence: 99%
“…The use of hybridization to pair ligand and gain in affinity through cooperative interactions with a target is well established. [29][30][31][32][33][34] However, the majority of studies reported so far used relatively long duplexes to achieve stable pairing between ligands. We showed that in one case, this could be reduced to an extremely short length PNA oligomer (4-mer) while preserving the cooperativity.…”
Section: Resultsmentioning
confidence: 99%
“…¾hnlich gingen Abendroth et al bei Untersuchungen des Östrogenrezeptors vor (siehe Abbildung 14 in Abschnitt 3.2.3). [140] Die DNA-programmierte räumliche Rasterung lieferte außer dem Abstand der Konsensusbindungstaschen für Östrogen auch Hinweise auf eine zusätzliche hydrophobe Bindungsstelle auf der Oberfläche der Ligandenbindungsdomäne.…”
Section: Pna/dnaunclassified